The results of surgical treatment of a patient with isolated left ventricular apical hypoplasia and left ventricular noncompaction - V. I. Skidan; Kh. A. Bsharat; Yu. I. Aseeva; G. P. Nartsissova; E. N. Pavlyukova (Российский кардиологический журнал, 2019)
There is a presentation of the results of a two-year follow-up after surgical treatment of a patient with chronic heart failure and a permanent form of atrial fibrillation, in which isolated apex hypoplasia and non-compaction of left ventricular myocardium were revealed.